Elastic Response of an Optimal Tensegrity-Type Metamaterial - De Tommasi, Domenico; Puglisi, Giuseppe; Trentadue, Francesco (Frontiers in Materials, 2019)
We study the elastic response of a class of optimal planar metamaterials designed as periodic patterns of tensegrity cells. Specifically, we consider an infinite slab constituted by prismatic cells whose sections on the middle plane are regular hexagons, squares or equilateral triangles subjected to a uniform normal stress. An attracting property of the proposed metamaterial is a very small tangential stiffness compared with the normal one. This property suggests the design of innovative isolation devices with extreme properties.